"Enough of Being Basely Tearful": "Glitter and Be Gay" and the Camp Politics of Queer Resistance. Issue 4 (27th October 2016) - JONES, MATTHEW J.
Abstract: Upon its publication in 1759, Voltaire's Candide, or The Optimist scandalized Europe. Banned for its blasphemous and politically seditious content, it became a succès de scandale and one of the most widely read books of its time. Leonard Bernstein adapted Voltaire's work for the stage in the 1950s. With its emphasis on the improbable, the artificial, and the insouciant, Candide practically begs for a camp (re)interpretation, and it is just such an analysis I offer here. After outlining camp as social critique, I turn to Cunégonde's aria "Glitter and Be Gay" and trace its path through camp's causeways in two different decades: first, in the United States of the 1950s, a period marked by McCarthy's witch-hunts, Cold War anxieties, intense homophobia, and the composer's personal struggle to accept his homosexuality, and second, in the late 1980s, when singer, songwriter, and AIDS activist Michael Callen (1955–1993) recorded his own camped-up version of "Glitter and Be Gay" for what would become his last musical project, a posthumous double album entitled Legacy (1996). By following Cunégonde's sparkling trail of glitter and gemstones through two historical moments, I demonstrate how camp functions as a tool of queer resistance across the last half of the twentieth century.